Training on Making Eco Enzymes from Fruit Waste in Suka Damai Village, Kuala Sub-District, Langkat District - Muhammad Wasito; Hendry; Ranti Eka Putri (International Forum of Researchers and Lecturers, 2023)
Ekoenzyme or Eco enzyme (EE) is the result of fermentation from organic waste in the form of vegetables or fruits, Ecoenzyme products are environmentally friendly products, easy to use, and easy to manufacture, and multi-functional, can be used to increase plant nutrients, so that the soil becomes more fertile, to clean the surrounding environment (environmental sanitation), to clean. mop the floor, clean yourself (bathing, brushing teeth, and others) and to provide air, all of which boils down to helping save our earth. Household organic waste is generated by many people every day. Therefore, one of the efforts for waste management is needed to increase the knowledge of the community in the village of Suka Damai, namely additional information and knowledge and awareness of the community group will make EE as one of the multi-functional products, which can overcome the problem of a lot of waste or organic waste, especially in households, The effort is to overcome and protect the environment, which has a good positive effect that can also be used to fertilize the soil. . The method of this activity was carried out using lecture and discussion methods, as well as hands-on practice. The results of this EE making training can help the community in managing organic waste, both fruit and vegetable waste.